Penggunaan Konsep Arsitektur Hijau Sebagai Perancangan Akademi Sepak Bola Pontianak: Bahasa Indonesia - Andeng; Theresia Ratna Darmiwati; Heristama Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2025)
The football academy in the city of Pontianak has the goal of fostering players at a young age which is carried out in stages as a solution for finding young players in Indonesia, especially in the city of Pontianak. The development of young players requires a variety of very adequate supporting facilities as a proper place for training and learning to provide comfort for the development of young players. Therefore the approach to designing a football academy in the city of Pontianak uses the concept of green architecture that is friendly to the environment. The results of the design of the football academy in the city of Pontianak emphasize the application of green architecture to design by increasing green open areas, vertical gardens, water treatment, solar panels and cross ventilation. Disbursement of data using the method of literature study, literature study, and precedent studies. The results of the design are that it can provide increased coaching for young players, can increase the added value of buildings, are climate responsive, environmentally friendly and sustainable buildings. Another hope is that this design can be a reference for other designers in the process of designing a building with a function as a sports area that applies the concept of environmentally friendly green architecture by paying attention to land use, maximizing the use of natural resources, being able to adapt to climate and as a conservation area.